Experimental Verification of Vehicle-to-Grid Charger for Demand Response Service - Tan K.M.; Ramachandaramurthy V.K.; Yong J.Y.; Tariq M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Electric load flow; Electric power system control; Electric power transmission networks; Electric power utilization; Electric vehicles; Vehicle-to-grid; Battery health; Bidirectional power flow; Demand response; Energy management algorithms; Experimental verification; Grid-connected; Laboratory experiments; Over charging; Secondary batteries